Regional anesthesia/analgesia and the risk of cancer recurrence and mortality after prostatectomy: a meta-analysis. (September 2015) - Lee, Brenda M; Singh Ghotra, Vinny; Karam, Jose A; Hernandez, Mike; Pratt, Greg; Cata, Juan P
Aims: To determine whether the use neuraxial anesthesia/analgesia is associated with longer biochemical recurrence-free survival (BRFS) and overall survival (OS) after radical prostatectomy.Methods: Ten studies were included in the meta-analysis. A random-effects model was used to estimate the hazard ratios (HRs).Results: The HR for BRFS was 1.02 (95% CI: 0.91–1.15) for all studies and 1.08 (95% CI: 0.91–1.15) for those that included propensity score matching. For OS, the HR across all studies was 0.91 (95% CI: 0.7–1.15) and 0.81 (95% CI: 0.68–0.96; p = 0.016) for those reporting propensity score matching.Conclusion: The anesthetic technique used during oncologic prostatectomy surgery is not associated with longer BRFS. By contrast, the use of regional analgesia appears to improve OS.